Dinamika Sosiolinguistik dalam Konsumsi Modern: Eksplorasi Kualitatif terhadap Bahasa Inggris sebagai Prestigious Code pada Citra Merek Lokal di Kota Tebing Tinggi - Nada Nabilah; Fitrianingsih Fitrianingsih (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2026)
This study investigates the convergence between sociolinguistics and consumer behavior in the emerging market ecosystem of Tebing Tinggi City. Focusing on the use of English as a prestigious code, the study employs a qualitative phenomenological approach to understand how foreign languages ​​are constructed as symbolic instruments to enhance local brand value. Data were collected through in-depth interviews with 10 urban informants in Tebing Tinggi and participant observation at various modern culinary and retail outlets. Findings indicate that the use of English diction triggers perceptions of